2014
DOI: 10.1371/journal.pone.0091680
|View full text |Cite
|
Sign up to set email alerts
|

ZiBuPiYin Recipe Protects db/db Mice from Diabetes-Associated Cognitive Decline through Improving Multiple Pathological Changes

Abstract: Multiple organ systems, including the brain, which undergoes changes that may increase the risk of cognitive decline, are adversely affected by diabetes mellitus (DM). Here, we demonstrate that type 2 diabetes mellitus (T2DM) db/db mice exhibited hippocampus-dependent memory impairment, which might associate with a reduction in dendritic spine density in the pyramidal neurons of brain, Aβ1-42 deposition in the prefrontal cortex (PFC) and hippocampus, and a decreased expression of neurostructural proteins inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 43 publications
3
35
1
Order By: Relevance
“…After 8 weeks of treatment, mice were fasted for 6 h (8:00 AM to 2:00 PM), and the oral glucose tolerance test (OGTT) and intraperitoneal insulin tolerance test (IPITT) experiments were performed as previously described (Chen et al, 2014b; Wang C. et al, 2014). Briefly, the animals were orally administered with glucose (2 g kg -1 body weight) or intraperitoneally administrated with insulin (0.75 U kg -1 body weight), and blood glucose levels were monitored over a 2 h period using Omron Glucometer.…”
Section: Methodsmentioning
confidence: 99%
“…After 8 weeks of treatment, mice were fasted for 6 h (8:00 AM to 2:00 PM), and the oral glucose tolerance test (OGTT) and intraperitoneal insulin tolerance test (IPITT) experiments were performed as previously described (Chen et al, 2014b; Wang C. et al, 2014). Briefly, the animals were orally administered with glucose (2 g kg -1 body weight) or intraperitoneally administrated with insulin (0.75 U kg -1 body weight), and blood glucose levels were monitored over a 2 h period using Omron Glucometer.…”
Section: Methodsmentioning
confidence: 99%
“…Traditional Chinese medicine (TCM) plays an important role in clinical treatment by providing multicomponent, multi-pathway, and multi-target regulation with fewer side effects. 11 We also previously determined the content of volatile oils and polysaccharides in ZBPYR using gas chromatography/mass spectrometry (GC/MS) and sulfuric acid-anthrone colorimetry, respectively. [1][2][3] For example, Zibu Piyin Recipe (ZBPYR) is a TCM formula prescribed to treat amnesia.…”
Section: Introductionmentioning
confidence: 99%
“…One barrier that we encountered when using the Lepr db/db model is that these mice have a substantially decreased lifespan (approximately 15 to 16 months) and can develop severe complications associated with obesity and metabolic dysfunction. It is occasionally observed that db/db mice have deficits in the Morris water maze (Chen et al, 2014), these studies are mostly confined to younger animals (~3 months of age) than those used in the current study (~6 months). Although the precise reason for this discrepancy is beyond the scope of the current study, these deficits are typically quite small, and it is possible that they are transitory and can be compensated for as the mice mature.…”
Section: Discussionmentioning
confidence: 99%